Does the profile of income inequality matter for economic growth? - Sara Voitchovsky (Luxembourg Income Study (LIS), 2003)
This paper investigates the importance of the shape of the income distribution as a determinant of economic growth in a panel of countries. Using comparable data on disposable income from the Luxembourg Income Study, results show that aggregate inequality measures, such as Gini coefficients, can mask key features of the relationship between inequality and growth. In particular, inequality at the top end and bottom end of the distribution appear to have opposite effects on growth. This finding supports the argument that the profile of the income distribution, and not only its spread, helps define the impact of inequality on growth.
Keywords: 330; Einkommensverteilung; Wirtschaftswachstum; Gini-Koeffizient; Westeuropa